2021
DOI: 10.3390/chemistry3030068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembling Properties of Peracetylated β-1-Triazolyl Alkyl D-Glucosides and D-Galactosides

Abstract: Carbohydrate-based low-molecular-weight gelators (LMWGs) are useful classes of compounds due to their numerous applications. Among sugar-based LMWGs, certain peracetylated sugar beta-triazole derivatives were found to be effective organogelators and showed interesting self-assembling properties. To further understand the structural influence towards molecular assemblies and obtain new functional materials with interesting properties, we designed and synthesized a library of tetraacetyl beta-1-triazolyl alkyl-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Fluorescence emission spectra were obtained using the Shimadzu RF-6000 Spectro Fluorophotometer with excitation and emission bandwidths set at 5.0 nm and a scan speed of 600 nm/min. The gelation tests, optical microscopy, and AFM imaging were carried out following a literature report [ 46 ]. The instruments used for optical microscopy was the Olympus BX60M optical microscope and the Olympus DP73-1-51 high-performance 17MP digital camera with pixel shifting and Peltier cooling.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence emission spectra were obtained using the Shimadzu RF-6000 Spectro Fluorophotometer with excitation and emission bandwidths set at 5.0 nm and a scan speed of 600 nm/min. The gelation tests, optical microscopy, and AFM imaging were carried out following a literature report [ 46 ]. The instruments used for optical microscopy was the Olympus BX60M optical microscope and the Olympus DP73-1-51 high-performance 17MP digital camera with pixel shifting and Peltier cooling.…”
Section: Methodsmentioning
confidence: 99%
“…Further, these hydrogels were implemented to study the controlled release of chloramphenicol and entrapment of dye. 105,106 A series of phenylboronic esters-based glycolipids were prepared using phenylboronic acid and alkylglucosides in a single step. After evaluating their gelation behavior, it was observed that these soft materials can be used for controlled release and drug delivery [Figure 14, (28)].…”
Section: Glycolipid Gelators Based On Monosaccharidesmentioning
confidence: 99%
“…A series of glycolipids was prepared, and their gelation and self-assembling characteristics were studied, along with the effect of structural variations. Further, these hydrogels were implemented to study the controlled release of chloramphenicol and entrapment of dye. , …”
Section: Glycolipid-based Gelatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The beta-glucosyl derivatives with triazole functional group linked through a 2 carbon spacer were also reported, some of the compounds are organogelators but the structure flexibility tend to make the molecules more soluble and less prone to form gels. 6 Isoxazoles are five membered ring heterocycles which can be synthesized via 2+3 cycloaddition reactions. 7,8 We envisioned that the nitrogen and oxygen containing isoxazole heterocycle could be used for the design of sugar based molecular gelators through modification of template B.…”
mentioning
confidence: 99%